Pengaruh Subtitusi Tepung Jagung Dalam Pembuatan Sosis Ikan Bandeng Dengan Penambahan Bubuk Daun Jeruk Purut - Dahlan, Sakinah; Isima, Putri (Jambura Journal of Food Technology, 2023)
Sausages made from fish are a processed seafood product created from fish paste (surimi), mixed with various seasonings, and then packaged using goat intestines or a similar material known as casing. Essentially, any type of fish, whether from freshwater or seawater, can be processed into sausage form. However, typically, the fish used as raw material for sausage processing consists of non-economic bycatch varieties. This research is designed using a Completely Randomized Design with one factor, which is the concentration of Kaffir lime leaf powder. The study includes one control and three treatments, with parameters such as Total Plate Count and Antioxidant testing. Based on the results, the Total Plate Count for the 9% concentration is 1700 x 102 CFU/g, and the highest antioxidant content in milkfish sausages with the addition of Kaffir lime leaf powder at 9% is 44.91 ppm